ANALISIS PARTISIPASI POLITIK MAHASISWA PPKN UNIVERSITAS ABULYATAMA SEBAGAI PEMILIH PEMULA PADA PILKADA 2024 - Muhammad Riski Muhammad Riski (Lembaga Sepercenter, 2025)
This research aims to analyze the political participation of first-time voters in the 2024 simultaneous regional elections among students of the Civic Education Study Program at Abulyatama University. The study employed a descriptive qualitative method with 10 informants selected through purposive sampling. Data were collected through interviews, observation, and documentation, and analyzed using Miles & Huberman's interactive model (data reduction, data display, and conclusion drawing). The findings reveal that political participation among novice voters varies significantly. Most students demonstrate high political awareness and actively participate in elections driven by democratic values and expectations for social change. However, some students remain apathetic due to distrust in political candidates and the electoral system. Obstacles identified include limited political literacy, environmental influences, and inadequate technical facilities during elections. This study highlights the importance of enhancing political education within universities and strengthening institutional support to foster novice voters’ political participation.